1998
DOI: 10.1172/jci1050
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IL-12 production by 1,25-dihydroxyvitamin D3. Involvement of NF-kappaB downregulation in transcriptional repression of the p40 gene.

Abstract: Interleukin 12 (IL-12), produced by myelomonocytic cells, plays a pivotal role in the development of T helper 1 (Th1) cells, which are involved in the pathogenesis of chronic inflammatory autoimmune disorders. 1,25-Dihydroxyvitamin D3 [1,25(OH)2D3] inhibits IL-12 production by activated macrophages and dendritic cells, thus providing a novel interpretation to its immunosuppressive properties. 1,25(OH)2D3 significantly inhibits mRNA expression for both IL-12 p35 and p40 subunits acting at the transcriptional le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
290
1
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 605 publications
(309 citation statements)
references
References 66 publications
13
290
1
5
Order By: Relevance
“…Quantitative RT-PCR analysis of 1␣-OHase, VDR, and 25(OH)D 3 ase) mRNA expression 1␣OHase, VDR, and 24(OH)ase mRNA levels were analyzed using an ABI 7700 sequence detection system (PE Biosystems, Warring, U.K.) using previously reported protocols (12). RNA was extracted from cell pellets using the StrataPrep total RNA miniprep kit (Stratagene, Amsterdam, The Netherlands) and was reverse-transcribed using AMV reverse transcriptase (Promega, Madison, WI) and random hexamers in 40-l reaction volumes according to manufacturer's instructions.…”
Section: Phospho-p38-immunoblotsmentioning
confidence: 99%
See 3 more Smart Citations
“…Quantitative RT-PCR analysis of 1␣-OHase, VDR, and 25(OH)D 3 ase) mRNA expression 1␣OHase, VDR, and 24(OH)ase mRNA levels were analyzed using an ABI 7700 sequence detection system (PE Biosystems, Warring, U.K.) using previously reported protocols (12). RNA was extracted from cell pellets using the StrataPrep total RNA miniprep kit (Stratagene, Amsterdam, The Netherlands) and was reverse-transcribed using AMV reverse transcriptase (Promega, Madison, WI) and random hexamers in 40-l reaction volumes according to manufacturer's instructions.…”
Section: Phospho-p38-immunoblotsmentioning
confidence: 99%
“…C hanges in dendritic cell (DC) 3 function represent the net cellular response to a large repertoire of microenvironmental positive and negative stimuli (1). An understanding of how developing or terminally differentiated DCs integrate these signals is of crucial importance in terms of defining regulatory pathways that contribute to the homeostatic control of their functions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in the current study, we observed an up-regulation of il-12p40 and tnf-a in VDR null DCs, as compared to WT and VDR DAF-2 DCs. The ligand-VDR complex is known to interfere with the signaling of transcription factors such as the nuclear factor of activated T cells (NFAT) and nuclear factor kB (NF-kB) [25,26], via obstruction of its activation and genomic binding, which results in the 1a,25 (OH) 2 D 3 -mediated down-regulation of il-12p40 [27,28]. In addition, reduced levels of the inhibitor of NF-kB were observed in VDR null cells [29].…”
Section: Discussionmentioning
confidence: 99%